Projeto de controle e otimização de um sistema de geração de vapor com múltiplas caldeiras com simulação dinâmica - Rosa, Eduardo Ledoux (2013)
This study proposes to develop a control project for a multiple boilers steam generation system that includes fuel optimization. To achieve that, it must combine an efficient boiler regulatory control and an efficient mechanism for load allocation to each boiler in order to operate with normally required reliability and combined with optimum fuel consumption. This dissertation presents: dynamic modeling of an industrial watertube boiler; computational implementation of the dynamic watertube Boiler model in Matlab, the control design of a watertube Boiler in 800xA automation system involving the definition of control strategies, communication of the 800xA automation system with the plant model in Matlab, an evaluation of some techniques for PID tuning including dynamic simulation results, the optimization problem to minimize the total fuel consumption of a multiple boilers steam generation system, as well as the assessment of their resolution with Mixed Integer Linear Programming modeling approach, and control design of a multiple boilers system, also involving dynamic simulation. Based on simulated experiments it was found that the control strategy proposed in this work has satisfactory performance, mainly because of the inclusion of the divider block load did not affect the rejection of disturbances characteristic, which encourages further studies with objective of practical use.